Item-specific patterns of the Skindex-17 in individuals with different levels of Hidradenitis Suppurativa severity: a network analysis study - Raimondi, Giulia; Samela, Tonia; Fania, Luca; Abeni, Damiano (Frontiers in Public Health, 2023)
Background Recent studies are stressing the idea that the level of Hidradenitis Suppurativa (HS) severity does not always correspond to the same illness load. In fact, it was found that there was no significant association between Skindex-17 and clinical severity of HS, and that some items of the Skindex-17 might be more related to HS severity than others. Objective The aim of the current study was to explore the associations between different levels of clinical severity of HS (mild, moderate, severe) and the Skindex-17 single-item responses in a large sample of adults patients. Methods A cross-sectional study with a sample include 547 consecutive HS patients, approaching for the first time the specific dermatologic evaluation. Eligible criteria included age ≥ 18 years, HS diagnosis formulated contextually by the same expert clinician, and providing informed consent. All participants completed the Skindex-17 and were evaluated for the disease clinical severity with the International Hidradenitis Suppurativa Severity Score System. A Network Analysis was conducted, which represents a powerful methodological approach in clinical research. It allows to study specific patterns and the structure of complex system in order to better understand how the elements of the system interact with each-other. Three different Network Analyses were conducted for each group of HS clinical severity by including the items of the Skindex-17 as the nodes of each network. Results Among 547 patients, 40% (219) were female and mean age was of 32.70 (±11.41). Different patterns among items of the Skindex-17 for the three clinical severity groups emerged, meaning that in each group different items are more crucial than others. The psychosocial subscale of the Skindex-17 is the most relevant when assessing the Quality of Life of individuals with different levels of HS severity, however, with the progression of the disease, individuals place attention also on two different aspects of the symptoms subscale of the Skindex-17, irritation and pain, which in turn perfectly reflect the severity of HS, from a clinical perspective. Conclusion These results provide new insights on the association between levels of HS severity and related Quality of Life, measured with the Skindex-17.